Advances in Computing and Communications First International Conference, ACC 2011, Kochi, India, July 22-24, 2011. Proceedings, Part I - Abraham, Ajith; Lloret Mauri, Jaime; Buford, John F.; Suzuki, Junichi; Thampi, Sabu M. (Springer eBooks., 2011)
This volume is the first part of a four-volume set (CCIS 190, CCIS 191, CCIS 192, CCIS 193), which constitutes the refereed proceedings of the First International Conference on Computing and Communications, ACC 2011, held in Kochi, India, in July 2011. The 68 revised full papers presented in this volume were carefully reviewed and selected from a large number of submissions. The papers are organized in topical sections on ad hoc networks; advanced micro architecture techniques; autonomic and context-aware computing; bioinformatics and bio-computing; cloud, cluster, grid and P2P computing; cognitive radio and cognitive networks; cyber forensics; database and information systems.